Performance Evaluation of Chinese Commercial Banks Based on the Malmquist Index - Xie, Wenjing; He, Meiling; Huang, Guohui; He, Lu; Lin, Fan; Pan, Wen-Tsao (Financial Risk and Management Reviews, 2021)
Commercial banks have the function of promoting the raising and rational distribution of funds in economic construction in China. Commercial banks are also important in promoting the smooth development of socialist economic activities and the development of national economy and other socialist productive economic activities. At present, one of the biggest difficulties faced by China's commercial banks is the improvement of their efficiency and competitiveness in the face of continuous development and change. This paper establishes the efficiency evaluation model of commercial banks using the DEA-based Malmquist index; it also uses a data envelopment analysis (DEA) to analyze the financial data of nine listed banks in China from 2011 to 2020, studies the efficiency of commercial banks in China, and finds the efficiency differences. Based on empirical research, this paper puts forward corresponding suggestions. The research shows that the key to dealing with this situation depends on the banks’ effective utilization of scientific and technological innovation and technological progress. In order to achieve the goal of innovative and sustainable development of commercial banks, it is necessary to integrate the continuous developments of science and technology with finance.